PEMANFAATAN TEKNOLOGI KOMUNIKASI MELALUI SISTEM INFORMASI MANAJEMEN DI PONDOK PESANTREN NUR EL FALAH - Uus Muhammad Husaini (Universitas Serang Raya, 2020)
ABSTRACT Islamic boarding schools are often seen as educational institutions that are still lagging behind in the utilization of communication technology. The connectivity that exists between stakeholders is manual and face-to-face. There have not been any Islamic boarding schools in Serang Regency that utilize communication technology through a fairly comprehensive management information system. This study aims to determine the Utilization of Communication Technology through Management Information Systems at Nur El Falah Islamic Boarding School, Kubang, Petir, Serang Regency, Banten. This research uses a qualitative approach with descriptive methods. The data was collected through observations and interviews with the management of the pesantren, religious teachers, foster caregivers, parents / guardians of the students. Data analysis using descriptive analysis. The results showed that the Nur El Falah Islamic Boarding School has utilized communication technology to build connectivity among stakeholders. Through the santri information system, stakeholders can control and supervise easily in accordance with their main duties and functions. Adaptation constraints that occur are overcome by socializing and strengthening supporting facilities. But even so, the head of the Nur El Falah Islamic Boarding School has a strong commitment to optimizing the use of communication technology through the information system of the students. Keyword: Utilization, communication technology, management information system, islamic boarding school ABSTRAK Pondok Pesantren sering dianggap sebagai lembaga pendidikan yang masih tertinggal dalam bidang pemanfaatan teknologi komunikasi. Konektivitas yang terjalin antara pemangku kepentingan masih bersifat manual dan tatap muka. Belum ditemukan pondok pesantren di Kabupaten Serang yang memanfaatkan teknologi komunikasi melalui sistem informasi manajemen yang cukup lengkap. Penelitian ini bertujuan untuk mengetahui Pemanfaatan Teknologi Komunikasi Melalui Sistem Informasi Manajemen di Pesantren Nur El Falah, Kubang, Petir, Kabupaten Serang, Banten. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan melalui pengamatan dan wawancara terhadap pengelola pondok pesantren pesantren, ustaz, wali asuh, orang tua/wali santri. Analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa Pondok Pesantren Nur El Falah telah memanfaatkan teknologi komunikasi untuk membangun konektivitas diantara para pemangku kepentingan. Melalui sistem informasi santri, para pemangku kepentingan dapat melakukan kontrol dan pengawasan dengan mudah sesuai dengan tugas pokok dan fungsinya. Kendala adaptasi yang terjadi diatasi dengan melakukan sosialisasi dan penguatan sarana penunjang. Namun meskipun demikian, Pimpinan Pondok Pesantren Nur El Falah memiliki komitmen yang kuat agar pemanfaatan teknologi komunikasi melalui sistem informasi santri dapat berjalan optimal. Kata Kunci: Pemanfaatan, teknologi komunikasi, sistem informasi manajemen, pondok pesantren